Manifestations of internationalisation of public universities of economics in Poland regarding student mobility – findings - Teneta-Skwiercz, Dorota; Sobińska, Małgorzata (Przejawy umiędzynarodowienia publicznych uczelni ekonomicznych w Polsce w zakresie mobilności studentów – wyniki badań, 2022)
The article’s main objective was to identify the propensity of students to participate in foreign exchange programmes and the expectations they formulate towards the HEI (Higher Education Institution) in creating conditions conducive to foreign mobility. The article presents a broader context of this mobility, presenting in the first part considerations concerning the essence of the process of internationalisation of HEIs and the strategies created for this process. The research used a multi-method approach (survey method and desk research method), with data triangulation. The assessment of the models of the range of internationalisation of these universities indicated the use of elements of the ‘import’ and ‘export’ models. An important aspect of internationalisation is the foreign mobility of both employees and students. Although students perceive the importance of international exchange, their level of knowledge about exchange programmes and interest in foreign mobility is low.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2022; vol. 66, nr 2, s. 130-142
Keywords: internationalization strategy of a university; student mobility; university of economics; Poland; umiędzynarodowienie szkoły wyższej; mobilność studentów; uczelnia ekonomiczna; Polska